THE INFLUENCE OF PHYTOTHERAPY ON MACROPROLACTINOMA SIZE - TrogrliÄ‡, Ivo; TrogrliÄ‡, Dragan; TrogrliÄ‡, Zoran (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The study aims at demonstrating the efficiency of phytotherapy in macroprolactinoma downsizing. The comparison of phytotherapeutic (PT) efficiency leant on medical records submitted by the patients prior to the PT launch, indicating the diagnosis established based on the outcome of the nuclear magnetic resonance imaging (NMRI) and/or computed tomography (CT) of the affected site and bringing the results of field-of-vision examination and hormonal status determination. The insight into the documentation in reference provided the information on tumour size and prolactin levels. The data in reference were compared against medical records submitted following phytotherapy completion. This study brings the results of a five-year investigation into the influence of phytotherapy on the size of macroprolactinomas. In patients responsive to this kind of treatment, tumour regression was witnessed within 6 months of herbal remedy use. A substantial tumour downsizing was accompanied by vision restitution; namely, in a number of cases, sight impairments are the first indicators of tumour presence. The basic parameters used for phytotherapeutic efficiency estimation and follow-up were the size of the tumour and the state of the field-of-vision, established both prior to and following phytotherapy. The results of the study presented herein unequivocally demonstrated the efficiency of phytotherapy in macroprolactinoma tumour mass downsizing, providing therefore solid grounds for the implementation of phytotherapy as a novel treatment modality of this tumour cluster.